Aluminum Enhances Growth and Sugar Concentration, Alters Macronutrient Status and Regulates the Expression of NAC Transcription Factors in Rice - Moreno-Alvarado, Marcos; García-Morales, Soledad; Trejo-Téllez, Libia Iris; Hidalgo-Contreras, Juan Valente; Gómez-Merino, Fernando Carlos (Frontiers in Plant Science, 2017)
Aluminum (Al) is a beneficial element for some plant species, especially when used at low concentrations. Though some transcription factors are induced by exposure to this element, no data indicate that Al regulates the expression of NAC genes in rice. In this study we tested the effect of applying 0 and 200 µM Al on growth, chlorophyll, amino acids, sugars, macronutrient concentration and regulation of NAC transcription factors gene expression in 24-day-old plants of four rice (Oryza sativa ssp. indica) cultivars: Cotaxtla, Tres Ríos, Huimanguillo and Temporalero, grown hydroponically under greenhouse conditions. Twenty days after treatment, we observed that Al enhanced growth in the four cultivars studied. On average, plants grown in the presence of Al produced 140% more root dry biomass and were 30% taller than control plants. Cotaxtla and Temporalero showed double the root length, while Huimanguillo and Cotaxtla had three times more root fresh biomass and 2.5 times more root dry biomass. Huimanguillo plants showed 1.5 times more shoot height, while Cotaxtla had almost double the root dry biomass. With the exception of Tres Ríos, the rest of the cultivars had almost double the chlorophyll concentration when treated with Al, whereas amino acid and proline concentrations were not affected by Al. Sugar concentration was also increased in plants treated with Al, almost 11-fold in comparison to the control. Furthermore, we observed a synergic response of Al application on P and K concentration in roots, and on Mg concentration in shoots. Twenty-four hours after Al treatment, NAC transcription factors gene expression was measured in roots by quantitative RT-PCR. Of the 57 NAC transcription factors genes primer-pairs tested, we could distinguish that 44% (25 genes) showed different expression patterns among rice cultivars, with most of the genes induced in Cotaxtla and Temporalero plants. Of the 25 transcription factors up-regulated, those showing differential expression mostly belonged to the NAM subfamily (56 %). We conclude that Al improves growth, increases sugar concentration, P and K concentrations in roots, and Mg concentration in shoots, and report, for the first time, that Al differentially regulates the expression of NAC transcription factors in rice.